Use of machine learning and IoT for monitoring and tracking of livestock - Aunindita, Rudaba Farhin; Misbah, Muhammed Shiam; Joy, Sibbir Bin; Rahman, Md. Ashikur; Mahabub, Sad Ibn (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.